ClC chloride channels - Mindell, Joe (BioMed Central, 2001)
Chloride-conducting ion channels of the ClC family are emerging as critical contributors to a host of biological processes. These polytopic membrane proteins form aqueous pathways through which anions are selectively allowed to pass down their concentration gradients. The ClCs are found in nearly all organisms, with members in every mammalian tissue, yet relatively little is known about their mechanism or regulation. It is clear, however, that they are fundamentally different in molecular construction and mechanism from the well-known potassium-, sodium-, and calcium-selective channels. The medical importance of ClC channels - four inherited diseases have been blamed on familial ClC dysfunction to date - highlights their diverse physiological functions and provides strong motivation for further study.